Differential phenotypic and genotypic characteristics of qnrS1-harboring plasmids carried by hospital and community commensal enterobacteria. - Vien, L; Abuoun, M; Morrison, V; Thomson, N; Campbell, J; Woodward, M; Van Vinh Chau, N; Farrar, J; Schultsz, C; Baker, S (2011)
The qnrS1 gene induces reduced susceptibility to fluoroquinolones in enterobacteria. We investigated the structure, antimicrobial susceptibility phenotype, and antimicrobial resistance gene characteristics of qnrS1 plasmids from hospitalized patients and community controls in southern Vietnam. We found that the antimicrobial susceptibilities, resistance gene characteristics, and plasmid structures of qnrS1 plasmids from the hospital differed from those from the community. Our data imply that the characteristics of the two plasmid groups are indicative of distinct selective pressures in the differing environments.